The TACOS Technique: A Stepwise Protocol for Alveolar Ridge Augmentation Using Customized Titanium Mesh - Mauro Merli; Luca Aquilanti; Marco Merli; Giorgia Mariotti; Giorgio Rappelli (Medicina)
Background: Alveolar ridge resorption following tooth loss poses a significant challenge for successful dental implant placement. In cases of severe atrophy, bone augmentation is required to restore sufficient bone volume. This technical note outlines a detailed, stepwise surgical protocol for horizontal and vertical alveolar ridge augmentation using customized titanium mesh. Materials and Methods: The procedure includes precise mesh fitting, autologous bone grafting, and the application of bioactive agents to promote bone regeneration. Emphasis is placed on the technique’s feasibility, predictability, and the critical steps necessary for preventing complications. Results: The use of customized mesh ensures stability and improved bone regeneration outcomes, enabling clinicians to achieve successful implant placement even in severely atrophic ridges. Conclusions: The described protocol has demonstrated predictable results in both clinical and radiographic evaluations, offering an effective solution for complex bone augmentation cases.